Anti-inflammatory activity and metabolites profiling of aqueous stem bark extract of Ficus vogelii (Moraceae) in rats - Edwige Laure Lappa; Calvin Bogning Zangueu; Edwige Laure Nguemfo; Jacquy Joyce Kojom Wanche; Christelle Stephanie Sonfack; Annie Laure Magne Fongang; Dupont Naoussi Calvin-Tamdjo; Julia Jiménez-lópez; Eulogio J Llorent-Martínez; Alain Bertrand Dongmo (Elsevier, 2022)
Introduction: Ficus vogelii is a terrestrial tree, used in Cameroonian pharmacopeia to treat various inflammatory diseases such as rheumatism. Accordingly, the present work aimed at evaluating anti-inflammatory potential of Ficus vogelii aqueous extract and identified phytochemicals of interest. Methods: The characterization of the phytochemicals was carried out by HPLC-ESI-MSn. The anti-inflammatory potential of the aqueous extract of Ficus vogelii (100, 200, 400 and 600 mg/kg) was investigated using acute inflammatory models induced by chemicals, and chronic inflammatory models induced by formalin and Complete Freund Adjuvant (CFA) in rats. Results: Ficus vogelii significantly (p < 0.001) inhibited carrageenan-induced rat paw edema with maximum inhibitions of 75.86% (0.5 h), 82.41% (3 h) and 90.18% (6 h) at 100 mg/kg. This extract significantly (p < 0.001) reduced paw edema induced by histamine (54.10%), serotonin (54.06%), dextran (38.90%) and arachidonic acid (56.95%) respectively up to 1 h. Similarly, the extract significantly (p < 0.001) inhibited edema formation on the left paws of rats from day 2 up to 7 days post formalin injection, and significantly (p < 0.001) decreased paw edema of CFA-treated rats with the highest effect of 67.85% and 77.07% obtained on day 13 and day 21. Furthermore, the extract showed an antioxidant potential by improving the tissue levels of malondialdehyde, nitrites, superoxide dismutase and catalase. Phytochemicals analysis showed several compounds with isocitric acid (19%), trihydroxy-octadecenoic acid (18%), followed by dihydroxybenzoic acid, chlorogenic acid and vicenin-2 (8-9%). Oxylipins represented approximately 25% of the extract, thus being some of the compounds responsible for the observed activity. Conclusion: These results suggest that Ficus vogelii have anti-inflammatory effects on acute and chronic inflammation conditions.